European solidarity as boundary-making: A conjoint analysis of attitudes towards Islam in the context of the 'refugee crisis'. (June 2021) - Krzyzowski, Lukasz; Nowicka, Magdalena
The arrival of refugees from predominantly Muslim countries in the core of Europe has fuelled discussions on European solidarity. This article explores the sources of solidarity in Europe in the aftermath of the 'refugee crisis' of 2015. By focusing on migrants' attitudes towards refugees, the article considers solidarity in light of contradictory public discourses on refugees in Europe. Drawing on data from a survey among Polish migrants residing in Germany and applying a conjoint analysis, the article demonstrates that religion and gender are the main criteria for boundary-making between the respondents and the refugees. In this process, national and ethnic identities are subordinated to the idea of belonging to an imagined Christian community. Our results suggest that new exclusionary solidarities shaped by boundary-making between Christians and Muslim refugees are being established within Europe. As a result, Islamophobia emerges as a transnational European exclusionary project evading ethnic and national boundaries.